Diagnóstico e manejo da ascite secundária à cirrose em pediatria - Alexandre Rodrigues Ferreira (2016)
The most important cause of ascites in pediatric population is cirrhosis with portal hypertension. The presence of ascites is one of the evidences of advanced stages of liver diseases and poorer prognosis. The first sign of ascitis can be inappropriate weight gain and increased abdominal girth. Although, it can be asymptomatic at the beginning. Ultrasound is a sensitive imaging technique for the detection of ascites and abdominal paracentesis is a way to confirm the presence of ascetic fluid and detect bacterial peritonitis. The treatment of ascites aims, primarily, patient comfort. Small amounts of ascitic fluid that do not produce symptoms may require little or no treatment. Tense ascites causing respiratory compromise, should be treated promptly, and may need therapeutic paracentesis. Furosemide and Spironolactone are the most common diuretics prescribed for ascitis management. Spontaneous bacterial peritonitis (SBP) is a complication of ascites that commonly occurs in cirrotic patients with portal hypertention. It can be favored by small intestine bacterial overgrowth, damaged enteric motility and permeability. It is important to SBP be quickly diagnosed by paracentesis or culture, so antibiotic treatment can be promptly initiated. It presents with heterogeneous clinical features. Thus, it is recommended that diagnostic paracentesis be performed when ascites first appears, at the time of a hospitalization, or when there is clinical deterioration, unexplained fever, abdominal pain, encephalopathy, gastrointestinal bleeding, acute renal failure.